1999
DOI: 10.1074/jbc.274.33.23341
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Probes That Differentially Modulate Peroxisome Proliferator-activated Receptor α and BLTR, Nuclear and Cell Surface Receptors for Leukotriene B4

Abstract: Peroxisome proliferator-activated receptor ␣ (PPAR␣) is a nuclear receptor for various fatty acids, eicosanoids, and hypolipidemic drugs. In the presence of ligand, this transcription factor increases expression of target genes that are primarily associated with lipid homeostasis. We have previously reported PPAR␣ as a nuclear receptor of the inflammatory mediator leukotriene B 4 (LTB 4 ) and demonstrated an anti-inflammatory function for PPAR␣ in vivo (Devchand, P. R., Keller, H., Peters, J. M., Vazquez, M., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
62
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…Although more studies are needed to clarify this issue, the existence of distinct uptake systems for LTB 4 and LTD 4 at the sinusoidal membrane of hepatocytes has been previously demonstrated (45). Moreover, in addition to cell surface receptors, LTB 4 is known to bind to nuclear receptors (46). In summary, our results indicate that 5-LO products directly modulate two key steps in lipid transport within the hepatic cells: the expression of key genes involved in the uptake of free fatty acids (i.e., L-FABP) and the secretion of VLDL-TG and apoB under the control of MTP activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although more studies are needed to clarify this issue, the existence of distinct uptake systems for LTB 4 and LTD 4 at the sinusoidal membrane of hepatocytes has been previously demonstrated (45). Moreover, in addition to cell surface receptors, LTB 4 is known to bind to nuclear receptors (46). In summary, our results indicate that 5-LO products directly modulate two key steps in lipid transport within the hepatic cells: the expression of key genes involved in the uptake of free fatty acids (i.e., L-FABP) and the secretion of VLDL-TG and apoB under the control of MTP activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that various lipid mediators are ligands for PPARs, a family of nuclear receptors that can act as transcription factors. In particular, studies by Devchand et al (45,46) have suggested that LTB 4 is a ligand for PPAR␣ and that activation of PPAR␣ by LTB 4 may function to limit the inflammatory response. Since LTB 4 levels were reduced in the allografts in 5lo Ϫ/Ϫ recipients, our findings raise the possibility that interruption of LTB 4 activation of PPAR␣ in this setting might contribute to accellerated graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…LTB 4 12-HD catalyzes the conversion of LTB 4 into 12-keto-LTB 4 in the presence of NADP 1 , and plays an important role in inactivating LTB 4 . The cDNA contained an ORF of 987 bp that encodes a protein of 329 amino-acid residues with a 78% identity with porcine LTB 4 12-HD. The amino acids in the putative NAD 1 …”
mentioning
confidence: 99%
“…We have cloned cDNA for leukotriene B 4 12-hydroxydehydrogenase (LTB 4 12-HD)/15-ketoprostaglandin 13-reductase (PGR) from guinea-pig liver. LTB 4 12-HD catalyzes the conversion of LTB 4 into 12-keto-LTB 4 in the presence of NADP 1 , and plays an important role in inactivating LTB 4 .…”
mentioning
confidence: 99%